Establishing functionally important predators on crown-of-throwns starfish (Acanthaster spp.) - Morgan Pratchett (Ideas in Ecology and Evolution, 2025)
Population irruptions of crown-of-thorns starfish (CoTS; Acanthaster spp.) are one of the foremost causes of coral loss and reef degradation throughout the Indo west-Pacific. The seemingly recent and/or increasing frequency and severity of CoTS population irruptions is often attributed to declining abundance or function of putative predators. Accordingly, there has been extensive research on, and an ever-growing list of, potentially important predators on CoTS. The latest candidates are eagle rays (family Myliobatidae), which were observed feeding among coral rubble in shallow reef areas in Kanaky New Caledonia (see Kayal and Lenihan 2025). Assuming that these large benthic feeders can detect and consume juvenile CoTS, eagle rays could have the necessary feeding capacity to effectively regulate CoTS populations and/ or contribute to suppressing local CoTS densities. There is however, considerable research needed to establish the functional importance of eagle rays and other putative predators. Most critically, rates of predation and corresponding mortality need to be ascertained, both in areas where there are sustained low densities of CoTS and where there is high incidence and predictable recurrence of population irruptions.